Spontaneous Rupture of a Nonparasitic Hepatic Cyst Associated with Peritonitis. (8th October 1991) - Shipley, Patricia; Baylis, Barry; Hershfield, Noel; Lui, Robert; Wong, Norman CW
Abstract : The first report of a nonparnsitic cyst complicated by rupture and peritonitis is given. A 63-year-old female found to have a nonparasitic hepatic cyst was discharged from hospital when her symptoms of sharp intermittent pains in the right upper quadrant resolved spontaneously. Hours later, she was re-admitted with rupture and peritonitis. After hepatic cystojejunostomy (Roux-en-y) and T-tube placement in the common bile duct, the patient remains asymptomatic two years later.